Severe Dry Eye in Covid-19 Patients Subject to Oxygen Therapy: A Case Report - sahih Alnasab, Seyed saber; Moravej, Raheleh (Journal of Ophthalmic and Optometric Sciences, 2022)
Dry eye is a common problem that mainly affects affecting the adult population. In severe cases, it can lead to sterile corneal ulceration and perforation. We report a rare case of severe dry eye in a 50-year-old woman with COVID‑19 who that developed after using an oxygen therapy device . Despite the medical history of dry eye, the severity of the disease increased so that it did not respond to bandages contact lenses, antibiotics, and artificial tears without preservatives at two-hour intervals. However, autologous serum improved but blurred vision and severe pain was improved by autologous serum. Awareness of possible ocular complications related to oxygen ventilation is important essential because prompt diagnosis and treatment can prevent severe visual consequences. In this clinical case, the timely management prevented a serious eye complication following oxygen therapy.